Self-regulated learning and academic performance amongst UTM undergraduates - Mohd. Kosnin, Azlina; Hamdan, Abdul Rahim (2012)
The purpose of this study is to investigate the level of self-regulated learning behaviour of final year UTM, Skudai students, and its relationship with students academic performance. A total of 388 final year undergraduate students from technology, applied science and arts disciplines participated in this study. SRL was measured via the translated version of the Motivated Strategies for Learning Questionnaire (MSLQ) developed by Pintrich, et al. (1991). The overall mean of self-regulated learning of UTM students is moderate with the mean score of 3.60 while results show low to moderate positive relationships between SRL and academic performance (r’s ranged between 0.31 to 0.41). Although the literature suggests that the motivational dimension of SRL is the most influential dimension towards academic achievement in the Western culture, findings from this study (through multiple regression analyses) showed that the behavioral dimension plays a more vital role in determining academic achievement amongst UTM students. Significant differences in SRL are found between genders and areas of discipline. Girls are better in SRL as compared with boys, and SRL is most practiced by applied science students, followed by technology and art students.